Long-term effect of exposure to lower concentrations of air pollution on mortality among US Medicare participants and vulnerable subgroups: a doubly-robust approach. Issue 10 (October 2021) - Yazdi, Mahdieh Danesh; Wang, Yan; Di, Qian; Requia, Weeberb J; Wei, Yaguang; Shi, Liuhua; Sabath, Matthew Benjamin; Dominici, Francesca; Coull, Brent; Evans, John S; Koutrakis, Petros; Schwartz, Joel D
Summary: Background: Long-term exposure to air pollution has been linked with an increase in risk of mortality. Whether existing US Environmental Protection Agency standards are sufficient to protect health is unclear. Our study aimed to examine the relationship between exposure to lower concentrations of air pollution and the risk of mortality. Methods: Our nationwide cohort study investigated the effect of annual average exposure to air pollutants on all-cause mortality among Medicare enrolees from the beginning of 2000 to the end of 2016. Patients entered the cohort in the month of January following enrolment and were followed up until the end of the study period in 2016 or death. We restricted our analyses to participants who had only been exposed to lower concentrations of pollutants over the study period, specifically particulate matter less than 2·5 μg/m 3 in diameter (PM2·5 ) at a concentration of up to 12 μg/m 3, nitrogen dioxide (NO2 ) at a concentration of up to 53 parts per billion (ppb), and summer ozone (O3 ) at concentrations of up to 50 ppb. We adjusted for two types of covariates, which were individual level and postal code-level variables. We used a doubly-robust additive model to estimate the change in risk. We further looked at effect-measure modification by stratification on the basis of demographic and socioeconomic characteristics. Findings: We found an increased risk of mortality with all three pollutants. Each 1 μg/m 3 increase in annual PM2·5 concentrations increased the absolute annual risk of death by 0·073% (95% CI 0·071–0·076). Each 1 ppb increase in annual NO2 concentrations increased the annual risk of death by 0·003% (0·003–0·004), and each 1 ppb increase in summer O3 concentrations increased the annual risk of death by 0·081% (0·080–0·083). This increase translated to approximately 11 540 attributable deaths (95% CI 11 087–11 992) for PM2·5, 1176 attributable deaths (998–1353) for NO2, and 15 115 attributable deaths (14 896–15 333) for O3 per year for each unit increase in pollution concentrations. The effects were higher in certain subgroups, including individuals living in areas of low socioeconomic status. Long-term exposure to permissible concentrations of air pollutants increases the risk of mortality. Funding: The US Environmental Protection Agency, National Institute of Environmental Health Services, and Health Effects Institute.